Juridical Analysis of the Norm Gap for Child Grooming in Indonesian Criminal Law in the Digital Era - H. Abdul Lawali Hasibuan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The rapid development of digital technology has led to the emergence of new forms of crime that increasingly target children as a vulnerable group, one of which is child grooming. This offense involves psychological manipulation carried out by perpetrators to gradually establish emotional relationships with children, ultimately leading to sexual exploitation. The main issue in this context is the absence of explicit and specific legal provisions regulating child grooming within the Indonesian criminal law system. This condition creates a legal gap that results in less effective law enforcement and inadequate protection for children. This study aims to analyze the existence of legal gaps in the regulation of child grooming and their implications for child protection in the digital era. The research employs a normative legal method using statutory and conceptual approaches. The findings indicate that existing regulations remain fragmented and primarily focus on the consequences of crime, thus failing to address the early stages of grooming. This limitation creates difficulties in evidence assessment and the application of criminal sanctions. Therefore, legal reform is necessary to explicitly recognize child grooming as a distinct criminal offense in order to strengthen child protection mechanisms